Determinant Factors of Sustainability Reporting: A Study in Indonesian Green Index of Sri-Kehati - Adhitya Agri Putra; Nanda Fito Mela; Ferdy Putra (Jurnal Akuntansi Keuangan dan Bisnis, 2021)
This research aims to examine the determinant factors of sustainability report disclosure by sustainable firms. Sample consists of listed firms in Indonesian Green Index of Sri-Kehati 2015-2019. Research variables include sustainability report, regulation, industry sensitivity, analyst coverage, and information asymmetry. Data analysis uses logistics regression. Status of state-owned firms, sustainability finance regulation, industry sensitivity, analyst coverage, and information asymmetry have effect on sustainability report disclosure. In the context of legitimacy theory, sustainability report as a legitimacy of firms’ businesses that have to be linear with government, regulator, and public interests. As a political cost perspective; sustainability report is used to avoid any penalty costs from government and regulator. In the agency theory perspective, analyst role to reduce information asymmetry and support more information disclosure of sustainability report to the market.